Detecting worm attacks in cloud computing environment: Proof of concept - Kanaker H.M.; Madihah Mohd Saudi; Mohd Fadzli Marhusin (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS/WOS